Urban Green Infrastructure in Latin America – A strategy for Bogota courtyards - Julia Nerantzia Tzortzi; Maria Stella Lux; Natalia Pardo Delgado (Agathón)
Green infrastructure and nature-based solutions are crucial for the sustainable transformation of cities into more resilient and inclusive places. However, the planning and design of these interventions must be tailored to different urban environments and socioeconomic contexts. Despite being one of the most urbanised global areas, the Latin American and Caribbean region still needs to be more researched. In this regard, this contribution provides an analytical and design framework for integrating nature-based solutions in dense urban contexts for microclimate mitigation and improved usability. It is constructed by considering the morphological, historical, climatic, and administrative peculiarities of Latin America, and it has been applied and tested in the case study of Bogotá (Colombia). The result is a matrix for constructing design strategies based on three key attributes of outdoor spaces and four design components.